2022
DOI: 10.1136/rapm-2022-103688
|View full text |Cite
|
Sign up to set email alerts
|

Association between thoracic epidural block and major complications after pleurectomy/decortication for malignant pleural mesothelioma under general anesthesia

Abstract: IntroductionA curative-intent surgical procedure, pleurectomy/decortication, for malignant pleural mesothelioma is accompanied by a high incidence of major postoperative complications. Although epidural block, which suppresses nociception during and after surgery, reportedly has both benefits and disadvantages in terms of outcomes after thoracic surgery for other diseases, the effects of epidural block on major complications after pleurectomy/decortication have not been evaluated. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Higher values of NR averaged from the start to the end of surgery (mean NR), which are calculated using heart rate, systolic blood pressure, and peripheral perfusion index, were reportedly associated with a higher incidence of major postoperative complications, defined as a Clavien–Dindo Class ≥ IIIa, after gastrointestinal surgery ( Table 1 ) [ 44 ]. Mean NR values also increased in the order of severity of postoperative complications in patients undergoing total shoulder arthroplasty, gastrointestinal surgery, and thoracic surgery ( Figure 2 ) [ 44 , 45 , 46 , 84 , 85 ].…”
Section: Nociception Monitors and Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher values of NR averaged from the start to the end of surgery (mean NR), which are calculated using heart rate, systolic blood pressure, and peripheral perfusion index, were reportedly associated with a higher incidence of major postoperative complications, defined as a Clavien–Dindo Class ≥ IIIa, after gastrointestinal surgery ( Table 1 ) [ 44 ]. Mean NR values also increased in the order of severity of postoperative complications in patients undergoing total shoulder arthroplasty, gastrointestinal surgery, and thoracic surgery ( Figure 2 ) [ 44 , 45 , 46 , 84 , 85 ].…”
Section: Nociception Monitors and Postoperative Complicationsmentioning
confidence: 99%
“…Gray circles show individual data points. Data in this graph were obtained from [ 44 , 45 , 46 , 84 , 85 ]. Significant differences are defined at * p < 0.001 vs. no complications, and # p < 0.001 vs. minor complications.…”
Section: Figurementioning
confidence: 99%
“…The study includes patients who underwent P/D from January 2022 to April 2022, as well as those included in our previous study from March 2019 to December 2021. [ 4 ] While the duration of patient enrollment in the present study was longer than in the previous study, [ 4 ] the number of analyzed patients in the present study was smaller due to a large volume of missing data on differential WBC counts. Further investigations are needed to determine the precise mechanisms by which TEB exerts suppressive effects on major complications after P/D in a prospective randomized controlled study in the future.…”
Section: Discussionmentioning
confidence: 77%
“…A previous study reported that the incidence of postoperative complications, defined as Clavien-Dindo grade ≥ III, was 32.3 % in patients with TEB and 63.1% in patients without TEB. [4] We thus assumed that the probabilities www.md-journal.com of postoperative complications were 30% and 60% in patients with or without TEB in the present study. Required sample size was then estimated to be 42 participants in each group and 84 in total.…”
Section: Sample Size Calculationmentioning
confidence: 99%
See 1 more Smart Citation